Patient education in physiotherapy in total hip arthroplasty (THA) - The perspective of physiotherapists - Jäppinen, Anna-Maija; Hämäläinen, Harri; Kettunen, Tarja; Piirainen, Arja (Physiotherapy theory and practice, 2020)
There is limited knowledge about patients' and physiotherapists' perceptions of patient education in physiotherapy in hip arthroplasty. The aim of this study was to describe physiotherapists' conceptions of the patient education in physiotherapy needed by patients undergoing total hip arthroplasty. The data for this qualitative study were collected using group and individual semi-structured interviews. Seven physiotherapists were interviewed. The research data were analyzed using a phenomenographic method. Three categories of patient education in physiotherapy in hip arthroplasty were produced and the categories formed a hierarchy. The narrowest descriptive category was Schematic physiotherapy complying with the protocol. Identifying individual rehabilitation needs was the second category, and the third, widest category was Coaching home rehabilitation. The differences between the categories were described in four themes: 1) Moving; 2) Exercising; 3) Interaction in relation to patient; and 4) Health care system. According to the results, patient education in physiotherapy optimally aims to identify patients' individual rehabilitation needs, advice on coping at home and especially helping patients to be prepared for and capable of long rehabilitation for which they are themselves responsible. These findings resulting from descriptive categories can be utilized in developing education methods and physiotherapists' competence in patient education.